PENINGKATAN HASIL BELAJAR MENGGUNAKAN METODE TUTOR SEBAYA DALAM PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR - Radianti Radianti; Tahmid Sabri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe research aims to improve student learning outcomes, carried out using the Peer Tutor method in a qualitative descriptive type of classroom action research in stages. Pre cycle, cycle I and cycle II, 4 meetings. The results of the pre-cycle, 35% of the total 31 students, 11 people completed the KKM (75). 3.76. Then the second cycle of meeting 3 related to RPP 3.71, and implementation 3.88. Then the fourth meeting related to RPP 3.92, and implementation of 4.00. Improvement of learning outcomes from pre-cycle to cycle 1 and cycle 2, from planning and implementation of learning cycle I to cycle II, there was a change. It turns out that thematic learning research using peer tutoring methods is proven to improve elearning outcomes and students. Student Worksheet Data in the first cycle of 31 students 61% who completed, then in the second cycle 31 students scored above the number 75, meaning 100% reached the KKM target. From the data, it is proven that the use of peer tutoring methods on the theme 8 Neighborhoods of Our Friends, sub-theme 1 Humans and the Environment, can improve the learning outcomes of fifth grade students at the State Elementary School 07 Delta Pawan.Keywords: Peer Tutor Method, Thematic Learning Outcomes